The use of commercially available adhesive tapes to preserve cartilage and bone tissue integrity during cryosectioning - Maxwell A Serowoky; Divya D Patel; Jason W Hsieh; Francesca V Mariani (BioTechniques)
The use of fluorescent tags to monitor protein expression and to lineage-trace cells has become a standard complement to standard histological techniques in the fields of embryology, pathology and regenerative medicine. Unfortunately, traditional paraffin embedding protocols can substantially diminish or abolish the native emission signal of the fluorophore of interest. To preserve the fluorescent signal, an alternative is to use cryosectioning; however, this can often result in undesirable artefacts such as tearing or shattering – particularly for mineralized tissues such as bone and cartilage. Here we present a method of using a commercially available tape to stabilize murine femur tissue, thus allowing for cryosectioning of cartilage and bone tissues carrying fluorescent tags without the need for demineralization.